Structure-Behavior Study of a Family of "Hybrid Cyanine" Dyes Which Exhibit Inverted Solvatochromism - Caroli-Rezende, M (ROYAL SOC CHEMISTRY, 2016)
The inverted solvatochromism of twenty dyes containing an electron-donor phenolate conjugated with an electron-withdrawing nitro-substituted phenyl ring was analyzed in terms of the dye structure and substituents. Structural factors that increased the difference between the electrophilicities of the donor and acceptor moieties, or the donor-acceptor strength of the phenolate dyes, also increased the sensitivity of the dyes to solvent-polarity changes and red-shifted their solvatochromic absorption bands.